The at-Will Employment Paradigm: A Link Between Law and Economic Imperatives in the United States - Seyed Ali Mousavi (Law and Economy, 2025)
Cost savings, along with increased efficiency and effectiveness in the governance space, are considered to be the nexus of the modern economy and public administration; providing these factors in the face of legal guarantees of employment in the public sector is a challenge. The “at-will employment” paradigm in the United States can be seen as a response to this challenge; Therefore, the aforementioned paradigm has been examined using a descriptive-analytical and library method with the aim of identifying its role in creating a balance between economic requirements and legal guarantees of public employment. Based on the research findings, the paradigm of voluntary employment requires reform and more attention to legal guarantees.